Katekese Sekolah Menengah Mengenai Yesus Sebagai Sahabat Sejati dan Tokoh Idola Pada Peserta Didik Kelas XA SMAK Frateran Malang - Agnes Ranubaya, Fransesco; Meo, Yohanes Wilson B. Lena; Handoko, Petrus Maria (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2023)
Young people often idolize models or idols regarding their lifestyle and charm. It would be wonderful if that fascination was directed towards Jesus Christ, the Savior. Admiration for these individuals is often driven by their exceptional values, traits, character, abilities or appearance, which embody the aspirations and aspirations of the admirer. This admiration can also lead to a longing for a relationship with the idolized figure, either directly or indirectly. The research methodology used is a qualitative method. The data used in this research was collected from news sources, books, and journals. The findings in this study conclude that what is formulated as the main problem is answered that catechesis on